A mechanistic model to account for the Donnan and volume exclusion effects in ultrafiltration/diafiltration process of protein formulations. (14th December 2020) - Yu, Zhao; Moomaw, John F.; Thyagarajapuram, Nagarajan R.; Geng, Steven B.; Bent, Colin James; Tang, Yu
Abstract: Ultrafiltration/diafiltration (UF/DF) is a typical step in protein drug manufacturing process to concentrate and exchange the protein solution into a desired formulation. However, significant offset of pH and composition from the target formulation have been frequently observed after UF/DF, posing challenges to the stability, performance, and consistency of the final drug product. Such shift can often be attributed to the Donnan and volume exclusion effects. In order to predict and compensate for those effects, a mechanistic model is developed based on the protein charge, mass and charge balances, as well as the equilibrium condition across the membrane. The integrated UF/DF model can be used to predict both the dynamic behavior and the final outcome of the process. Examples of the modeling results for the pH and composition variation during the UF/DF operations are presented for two monoclonal antibody proteins. The model predictions are in good agreement with a comprehensive experimental data set that covers different process steps, protein concentrations, solution matrices, and process scales. The results show that significant pH and excipient concentration shifts are more likely to occur for high protein concentration and low ionic strength matrices. As a special example, a self‐buffering protein formulation shows unique pH behavior during DF, which could also be captured with the dynamic model. The capability of the model in predicting the performance of UF/DF process as a function of protein characteristics and formulation conditions makes it a useful tool to improve process understanding and facilitate process development.